CSR in German tech startups – a conceptual framework for effective CSR - Lenczowski, Dennis (2021)
This study examines corporate social responsibility (CSR) approaches of German tech startups. The aim of this study is to develop a framework which contains fundamental approaches for profound and effective CSR for tech startups which pays particular attention to the startups’ nature and development levels. In the context of this study, previous perceptions about corpo-rate social responsibility, its meanings, approaches, drivers, benefits and challenges are system-atically explained and compared. The study follows a qualitative research approach in the form of in-depth interviews with founders and CEOs of German tech startups which were following-ly contextualized according to identified themes. Even though tech startups see the benefits of responsible practices, they struggle to comprehend the concept from their individual perspective. CSR may be applied in tech startups; however, it often lacks official character. Hence CSR is not formally communicated to internal and external stakeholders which ultimately restricts its potential. In order to overcome these issues, this research illustrates a practical framework on the basis of literary and empirical findings, which helps tech startups to engage into meaningful and effective CSR. By developing and offering this framework to tech startups, the study wants to contribute to the responsible and sustainable development of young tech companies.